2008
DOI: 10.1177/1077559508322446
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Reach of Preventive Interventions

Abstract: There are major obstacles to the effective delivery of mental health services to poor families, particularly for those families in rural areas. The rise of Internet use, however, has created potentially new avenues for service delivery, which, when paired with the many recent advances in computer networking and multimedia technology, is fueling a demand for Internet delivery of mental-health services. We report on the adaptation of a parenting program for delivery via the Internet, enhanced with participant-cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 63 publications
1
32
0
Order By: Relevance
“…Parents were expected to attend the entire series of classes (typically 5-8). Other designs included booklet or printed material (Adachi et al, 2009;Jackson and Dickinson, 2009;McKellar et al, 2008), DVD or film-based (Brown, 2006) and Internet-based sessions (Brown, 2006;Feil et al, 2008;Kuo et al, 2009;Salonen et al, 2008). There was littleevidence to suggest that alternate forms of parent education were any more or less effective than traditional face-to-face methods (Salonen et al, 2008).…”
Section: Designmentioning
confidence: 97%
See 1 more Smart Citation
“…Parents were expected to attend the entire series of classes (typically 5-8). Other designs included booklet or printed material (Adachi et al, 2009;Jackson and Dickinson, 2009;McKellar et al, 2008), DVD or film-based (Brown, 2006) and Internet-based sessions (Brown, 2006;Feil et al, 2008;Kuo et al, 2009;Salonen et al, 2008). There was littleevidence to suggest that alternate forms of parent education were any more or less effective than traditional face-to-face methods (Salonen et al, 2008).…”
Section: Designmentioning
confidence: 97%
“…However, this is not typically the design of most parenting classes, where it is more usual for the facilitator to cover a comprehensive list of topics delivered over a number of weeks that may or may not pertain to issues actually being experienced by the parents at the time. In fact, in the interest of maintaining fidelity, programmes frequently dissuaded facilitators from modifying content (e.g., Feil et al, 2008;Hiscock et al, 2008;Rowe and Fisher, 2010;Sanders et al, 2002). In contrast, Svensson et al (2006) proposed that parents may engage in educational initiatives when they can choose topics that they find relevant.…”
Section: Participant/parent Engagement Attrition and Reachmentioning
confidence: 98%
“…The Baby-Net adaptation of PALS (Feil et al, 2008, 2014), replicating the original PALS in-home learning structure, includes the following key component structure in each intervention session: (a) self-directed learning of PALS skills through video-based examples and nonexamples, with check-in questions using immediate individualized feedback; (b) action plan outlining daily activity practice (homework) based on skills taught; (c) video-recorded practice creating a 5-min, computer-collected, mother–infant interaction video demonstrating skills learned and uploaded to a project server; and (d) coach call involving mothers and coaches coviewing weekly mother-created videos to provide individualized support for conceptual learning and skill acquisition. Prior to each coach call, coaches prepare by accessing weekly mother-created video and auto generated reports that display the amount of time mothers spend in the program and their responses to check-in questions.…”
Section: Methodsmentioning
confidence: 99%
“…To address financial and geographical barriers to intervention access (Katz, La Placa, & Hunter, 2007), we adapted the evidence-based PALS program (Landry et al, 2008) for Internet delivery with remote coaching for low-income mothers (e-PALS: Infant-Net; Baggett et al, 2010; Feil et al, 2014; Feil et al, 2008). Examination of Infant-Net within a randomized controlled pilot trial with 40 low-income mothers and their infants showed high retention and engagement with medium to large effects on maternal parenting practices and infant behavior (Baggett et al, 2010).…”
mentioning
confidence: 99%
“…Technology gives individuals greater freedom in how they choose to participate and fit an intervention into their daily routine. As a result, practitioners may spend less time rescheduling canceled or missed appointments (Feil et al, 2008;Self-Brown & Whitaker, 2008). Utilizing technological media, through which parents are becoming increasingly familiar, can potentially be cost-effective because many of these devices are already used in the home.…”
mentioning
confidence: 99%